Breech presentation at birth has short-term but no long-term effect on neurodevelopmental outcome in moderate and late preterm infants - Scheuchenegger, Anna; Einspieler, Christa; Marschik, Peter B.; Pansy, Jasmin; Sommer, Constanze; Resch, Bernhard (Early human development, 2025)
Aim - To investigate the effects of fetal presentation at birth on spontaneous postnatal movements, postures and neurodevelopmental outcome in moderate and late preterm (MLPT) infants. - Methods - The study population comprised 154 infants (55 % male, 55 % singletons) of whom 33 (21 %) were born in breech presentation. During the neonatal period and at 3-4 months post-term age, categorical Prechtl general movements assessment (GMA) and detailed scoring of motor functions was performed by means of the General Movement Optimality Score (GMOS) neonatally and Motor Optimality Score-Revised (MOS-R) later. Neurodevelopment was assessed at one year using Bayley-III. - Results - Infants born in breech presentation more frequently exhibited pathological GMs (p = 0.05) with increased stiffness in the lower extremities (p < 0.01) at neonatal age. Detailed motor assessments at 3-4 months post-term age (MOS-R) showed lower scores in infants born in breech compared to those with cephalic presentation at birth. Fetal presentation at the time of delivery did not impact neurodevelopmental outcomes at 12 months. - Conclusion - Breech presentation at birth affected GMs and movement assessments in the early postnatal period but had no persistent impact on neurodevelopmental outcomes at one year, suggesting a transient effect on lower extremity movements. Given stiffness in the extremities in neonates is an alarm sign and might relate to cramped synchronized GMs indicating an increased risk for cerebral palsy, fetal presentation at birth should be taken into consideration in neonatal neuromotor assessments.
Online verfügbar 1 April 2025, Version des Artikels 8 April 2025
Gesehen am 01.10.2025